2011
DOI: 10.1203/pdr.0b013e3182026370
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Oxidation Is Associated With Airway Macrophage Functional Impairment in Children With Severe Asthma

Abstract: Airway cellular dysfunction is a differentiating feature of severe asthma in children that may be related to an imbalance of the antioxidant, glutathione (GSH). We hypothesized that oxidation of GSH to glutathione disulfide (GSSG) in the epithelial lining fluid (ELF) of children with severe asthma would contribute to altered airway macrophage (AM) GSH homeostasis and AM cellular dysfunction. Bronchoalveolar lavage (BAL) was performed in 64 asthmatic children (severe asthma, n = 43). GSH, GSSG, markers of lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 30 publications
4
50
0
3
Order By: Relevance
“…On the other hand, 8-OHdG is an indicator of oxidative DNA damage and is formed when reactive OH attacks deoxyguanosine nucleotides in DNA [18]. Increased 8-OHdG levels have been observed in severe asthmatics [42]. In this study, we observed a consistent suppression of these oxidative damage biomarkers by artesunate in the inflamed lungs, suggesting that artesunate could markedly lessen reactive oxygen and nitrogen species in the lungs and prevent oxidant-induced lung damage.…”
Section: Discussionsupporting
confidence: 67%
“…On the other hand, 8-OHdG is an indicator of oxidative DNA damage and is formed when reactive OH attacks deoxyguanosine nucleotides in DNA [18]. Increased 8-OHdG levels have been observed in severe asthmatics [42]. In this study, we observed a consistent suppression of these oxidative damage biomarkers by artesunate in the inflamed lungs, suggesting that artesunate could markedly lessen reactive oxygen and nitrogen species in the lungs and prevent oxidant-induced lung damage.…”
Section: Discussionsupporting
confidence: 67%
“…Similarly, in a recent study, children with severe asthma had increased concentrations of glutathione disulfide (GSSG), a product of oxidized glutathione, compared with mild asthmatics (Fitzpatrick et al, 2011). Furthermore, this imbalance in GSH homeostasis was associated with decreased HDAC activity which is critically linked to steroid resistance, a characteristic feature of severe asthma.…”
Section: Discussionmentioning
confidence: 93%
“…Считают, что повышение концентрации GSSG, наблюдаемое при БА, обусловлено увели-чением активности гистоновых ацетилтрансфераз, подавлением активности гистоновых деацетилаз в клетках респираторного тракта. Повышение кон-центрации GSSG сопровождается усилением про-дукции провоспалительных цитокинов, в том числе и IL-8/CXCL8, рекрутирующего нейтрофилы [44], и развитием макрофагальной дисфункции [24]. Де-фицит GSH обусловливает ингибирование продук-ции Th 1 -ассоциированных цитокинов и активацию их синтеза [51], в то время как увеличение содержа-ния GSH в клетках респираторного тракта приводит к снижению содержания IL-4, -5, -10, эотаксина, CCL5/RANTES в жидкости бронхоальвеолярного лаважа и усилению продукции IL-12, IFN-γ [25].…”
Section: резюме в обзоре литературы изложены современные данные о спunclassified